Mathematics Performance Profiles and Relation to Math Avoidance in Adolescence: The Role of Literacy Skills, General Cognitive Ability and Math Anxiety - Kyttälä Minna; Björn Piia (Routledge, Taylor & Francis Group, 2022)
The main aim of the study was to differentiate adolescent profiles by math performance at the beginning and end of the final two years of lower secondary school, and relevant baseline attributes (literacy skills, general cognitive ability, math anxiety), and to investigate how these profiles differed by gender and math avoidance. A total of 193 Finnish lower secondary students participated in this study. Four profiles were identified: (1) High academic, average anxiety; (2) low academic, average anxiety; (3) average academic, high anxiety; and (4) average academic, average anxiety. They differed in baseline attributes, math performance over two school years, math avoidance, and in gender ratio. High levels of math anxiety was related to unfavourable math trajectory and future math avoidance. This high anxiety was typical of a certain group of average performers but not of the lowest performers. The educational implications of the findings are discussed.